(untitled) (Papeles, 2023)
With the aim of thinking about the professionalisation of Social Work promoted by the State of Santa Fe, in this article I analyse the relationship between professional training and autonomy in the second half of the 1940s. To do so, I start with the concept of autonomy and then focus on the state demand that gave rise to this new profession in Santa Fe: the reading of the social problems that were a priority at the time and the knowledge required from social workers to intervene in them. Finally, I focus my attention on the dispute for professional autonomy that arises between the authorities’ demand to train qualified agents to intervene in social issues subordinated to the government project and the position of the new professionals in defence of decision-making in the exercise of the profession (which in some aspects coincide with the mandates and in others question them).